Review of Cremnomymar species (Hymenoptera: Mymaridae) in mainland South America, with a new generic synonymy - Triapitsyn, Serguei V. (Zootaxa, 2024)
Parapolynema Fidalgo syn. n. (Hymenopterea: Mymaridae) is synonymized under the Neotropical genus Cremnomymar Ogloblin, and its two described species, both from Argentina, are transferred to Cremnomymar as C. sagittifer (Fidalgo) comb. n. and C. tucumanum (Fidalgo) comb. n. These species are redescribed based on type and non-type specimens from Argentina and two new species are described and diagnosed, C. fidalgoi Triapitsyn sp. n. from Argentina and Chile and C. nahuelbutae Triapitsyn sp. n. from Chile. A key to females of the four known species of Cremnomymar in mainland South America outside of Chile’s Juan Fernández Islands, from where seven other, endemic Cremnomymar species are known, is provided. The male of C. fernandezi Ogloblin is redescribed based on a non-type specimen from Robinson Crusoe Island, Juan Fernández Islands, and a possibly conspecific female from the same collecting event is described. The male paratype of C. kuscheli (Ogloblin) from Juan Fernández Islands is redescribed and illustrated.